Relevance of the Use Of Pedagogical and Innovative Technologies in Russian Lessons - Mamedrva Nargiza Ziraddinovna (Zien Journals, 2023)
This article discusses the role of pedagogical and innovative technologies in the organization of Russian language classes in higher educational institutions
Keywords: innovative technology; Russian language; method; efficiency